IRS-Assisted MC-NOMA System Communication Security Scheme - Yang, Zilong; Guo, Hui (International Journal of Computer Science and Information Technology, 2026)
To address the communication security of the Intelligent Reflecting Surface (IRS)-assisted Multicarrier Non-Orthogonal Multiple Access (MC-NOMA) system, a problem of maximizing the secure sum rate is formulated under the constraints of subcarrier allocation schemes, base station transmission power, and IRS phase shifts. The security performance of the communication system is enhanced by jointly alternating optimizing beamforming vectors and IRS phase shifts. Simulation results demonstrate that the proposed scheme exhibits significant advantages in improving the security and efficiency of communication systems.